Millionaire teacher : the nine rules of wealth you should have learned in school - Hallam, Andrew (Teacher) (John Wiley & Sons, 2017)
"Adopt the investment strategy that turned a school teacher into a millionaire Millionaire Teacher shows you how to achieve financial independence through smart investing -- without being a financial wizard. Author Andrew Hallam was a high school English teacher. He became a debt-free millionaire by following a few simple rules. In this book, he teaches you the financial fundamentals you need to follow in his tracks. You can spend just an hour per year on your investments, never think about the stock market's direction -- and still beat most professional investors. It's not about get-rich-quick schemes or trendy investment products peddled by an ever-widening, self-serving industry; it's about your money and your future. This new second edition features updated discussion on passive investing, studies on dollar cost averaging versus lump sum investing, and a detailed segment on RoboAdvisors for Americans, Canadians, Australians, Singaporeans and British investors. Financial literacy is rarely taught in schools. Were you shortchanged by your education system? This book is your solution, teaching you the ABCs of finance to help you build wealth. Gain the financial literacy to make smart investment decisions Learn why you should invest in index funds Find out how to find the right kind of financial advisor Avoid scams and flash-in-the-pan trends Millionaire Teacher shows how to build a strong financial future today." --